Development of an Emotional Intelligence test - Escurra Mayaute, Luis M. (2000)
Under the theoretical framework of Salovey and Moyer a psychometric test has been created to measure Emotional Intelligence. Five domains have been considered for items elaboration: a) Emotional Self-knowledge; b) Emotional Control; c) Self motivation; d) Empathy and e) Interpersonal relations. A randomly sample of 489 first level students was selected from 19 different University Programs which belong to five Academic Areas. The psychometric item analysis permited to take not statistically significant items out. The Test reported internal consistency reliability through Alfa Cronbach Coeficient. It has been reported for each domain evaluated and for the general test. It has been also confirmed content and construct validity for the test.